Analysis of plasma surfactant protein D levels in lung transplant recipients. Issue 6 (13th September 2013) - Bejvl, I.; Weseslindtner, L.; Strassl, R.; Jaksch, P.; Kundi, M.; Klepetko, W.; Puchhammer‐Stöckl, E.
Abstract In lung transplant recipients (LTRs), severe clinical complications, such as microbial infections of the lung or transplant rejection, may occur. Surfactant protein D (SP‐D) is a C‐type lectin that is mainly produced in alveolar type II cells. Plasma SP‐D levels are usually low, but may increase when the lung–blood barrier is impaired. In this study, we analyzed whether plasma SP‐D concentrations reflect rejection or infection of the lung allograft. An enzyme‐linked immunosorbent assay was used to measure SP‐D levels in plasma samples from 58 LTRs during intervals without pathologic respiratory findings and during episodes of acute cellular rejection (ACR), microbial colonization, and microbial pneumonia. Median plasma SP‐D levels were significantly increased during episodes of microbial pneumonia, but not in the absence of pathologic respiratory findings, during microbial colonization, or during ACR up to grade A2–A3 (P < 0.05). During pneumonia, an increased plasma SP‐D level was detected in 60% of LTRs and this was further associated with a significantly higher risk for the patients to develop stage III bronchiolitis obliterans syndrome (BOS III) or to die within the subsequent 6 months after pneumonia (P = 0.0093). All patients with a plasma SP‐D level of >300 ng/mL during pneumonia developed BOS III and/or died within 6 months of follow‐up (P = 0.001). The determination of SP‐D levels in plasma during pneumonia in LTRs may be of prognostic value and warrants further evaluation.